Holocene elephant seal distribution implies warmer-than-present climate in the Ross Sea - Hall, B. L.; Hoelzel, A. R.; Baroni, C.; Denton, G. H.; Le Boeuf, B. J.; Overturf, B.; Topf, A. L. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
We show that southern elephant seal (Mirounga leonina) colonies existed proximate to the Ross Ice Shelf during the Holocene, well south of their core sub-Antarctic breeding and molting grounds. We propose that this was due to warming (including a previously unrecognized period from approximate to 1,100 to 2,300 C-14 yr B.P.) that decreased coastal sea ice and allowed penetration of warmer-than-present climate conditions into the Ross Embayment. If, as proposed in the literature, the ice shelf survived this period, it would have been exposed to environments substantially warmer than present.
id: 1918; PT: J; NR: 25; TC: 14; J9: P NATL ACAD SCI USA; PG: 5; GA: 064DM; UT: WOS:000239069400013